Charge-Coupled Device Based on an Optical Tomography System for Monitoring Multiphase Flow - Jamaludin, Juliza; Abdul Rahim, Ruzairi; Fazalul Rahiman, Mohd Hafiz; Mohd Muji, Siti Zarina; Mohd Rohani, Jemmy; Abdul Wahab, Yasmin (International Journal of Integrated Engineering, 2017)
Tomography is a method to capture a cross sectional image based on the data obtained by sensors, distributed around the periphery of the analyzed system. Optical tomography is one of the tomography methods which are non-invasive and non-intrusive system, consisting of emitter with detectors. Combinations of Charge-Coupled Device and low intensity laser diode are used in this research. Experiments on air bubbles detecting in non-flowing crystal clear water are conducted. Cross-sectional image of two phase flow; air and liquid are captured using this optical hardware construction and the information on air diameter, shape and path are observed using LabVIEW programming.